THE ROLE OF NECROTIC AND APOPTOTIC CHANGES IN NEUTROPHILIC GRANULOCYTES IN THE DEVELOPMENT OF EXPERIMENTAL BACTERIAL-IMMUNE PERIODONTITIS - Demkovych, A.Ye. (World of Medicine and Biology, 2018)
Mechanisms of the inflammatory process development in the periodontal complex include a number of complicated processes leading to the generalization and chronicization, tooth loss and the appearance of complications from other organs. One of the key links in the immune system is cellular nonspecific immunity, which is not only instrument of an antiinfectious protection, but also a universal homeostasis effector. The article presents the results of studies of early and late apoptosis parameters of blood neutrophils on the 7th and 30th days of inflammatory process in periodontal tissues. The results were presented in percent (the ratio of the number of annexin-positive cells to the total number of neutrophil fraction) and were statistically processed using parametric and nonparametric methods of statistics. In this investigation a characteristic dynamics of changes in the number of cell death was revealed for formation of an inflammatory site in the periodontal complex. It is important to compare the results of the realization of necrosis and apoptosis of blood neutrophils in the experimental bacterial-immune periodontitis. In particular, the course of experimental periodontitis was accompanied by an increase in the content of annexin-positive (early apoptosis) and necrotic neutrophils, which is associated with increased intensity of their formation in response to antigen stimulation. In this modeled pathology, the realization of induced cell death occurred predominantly by apoptosis.